Human-Centered Design of a Low Molecular Weight Heparin Order Set to Reduce Medication Errors. Issue 1 (January 2019) - D'Souza, Anishka; Wu, Phillis; Jung, Laura; Nungaray, Karla; Richman, Mark
Abstract : ABSTRACT: Inpatient anticoagulation medication errors for venous thromboembolism (VTE) therapy are common. Our VTE Team identified frequent dosing and duplicate order errors for therapeutic-dose low molecular weight heparin, which (lacking computerized physician order entry) was ordered using blank forms. To decrease such errors, a nonmandatory order form with weight-based dosing and prechecked orders discontinuing existing injectable anticoagulation was developed using human-centered design innovation principles/processes emphasizing end-user engagement in all phases: observation, exploring solutions, and rapid prototyping/feedback. Three physicians independently reviewed ordering errors the year before versus after implementation. Before implementation, 11% of orders contained any error versus 10.5% after implementation ( p = .82); 6.2% had a dosing or duplicate therapy error versus 4.2% after implementation (all made when the form was not used; p = .19). No dosing or duplicate therapy errors were made when the form was used. Were the form mandatory, all such ordering errors would likely have been eliminated, leaving 11% before versus 6.3% after implementation orders with any error ( p = .015), and 6.2% before versus 0% after implementation orders with duplicate or dosing therapy errors ( p < .001). Human-centered design of an anticoagulation order form can reduce anticoagulation order errors; such principles can be applied to other health care innovations, including electronic order sets.